Preliminary evidence of the association between DNAm and orbital volumetry in GO. Issue 7 (July 2020) - Hu, Ya-Fen; Hua, Lin; Tuo, Xiu; Shi, Ting-Ting; Yang, Yi-Lin; Liu, Yun-Fu; Yan, Zhong-Yu; Xin, Zhong
Abstract : Background : The pathogenesis underlying the alterations of orbital architecture in Graves' orbitopathy (GO) is not yet fully understood. The present study aimed to investigate the association of DNA methylation in peripheral blood and orbital volumetry in Chinese patients with GO. Methods : A total of 35 GO subjects (70 orbits) were subjected to CT scan. The total cross-sectional area of the extraocular muscles (orbital muscles, OM), total orbit area (TOA), and the exophthalmometry were measured and OM/TOA ratio was calculated. Targeted bisulfite sequencing was performed on seven candidate genes. Results : No significant correlation was established between the DNA methylation levels of these genes and exophthalmometry. The MBP methylation level was found to be correlated with OM/TOA ratio ( P < 0.05). Multiple linear regression analysis on parameters including age, sex, TRAb, duration of GO, and DNA methylation levels of seven genes with OM/TOA ratio confirmed that MBP and OM/TOA ratio had a significant correlation ( P < 0.05). The partial least squares analysis showed that the top three genes with the highest loadings were MBP, BOLL, and BECN1 and that OM/TOA ratio affected the DNA methylation block than exophthalmometry. Conclusions : This study provided preliminary evidence that MBP is a potential gene associated with OM enlargement in GO patients according to the combination of DNA methylation sequencing and orbital CT measurement.